1995
DOI: 10.1074/jbc.270.44.26543
|View full text |Cite
|
Sign up to set email alerts
|

5-Lipoxygenase Products Modulate the Activity of the 85-kDa Phospholipase A2 in Human Neutrophils

Abstract: 14C]arachidonoylphosphatidylcholine as substrate. A similar increase in cytosolic PLA 2 activity was induced by stimulation of neutrophils with leukotriene B 4 (LTB 4 ), 5-oxoeicosatetraenoic acid, or 5-hydroxyeicosatetraenoic acid (5-HETE). LTB 4 was the most potent of the agonists, showing maximal effect at 1 nM. Inhibition of 5-lipoxygenase with either eicosatetraynoic acid or zileuton prevented the AA-induced increase in PLA 2 activity but had no effect on the response induced by LTB 4 . Furthermore, pretr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
41
0
1

Year Published

1996
1996
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(46 citation statements)
references
References 61 publications
4
41
0
1
Order By: Relevance
“…The simplest explanation for these events is that sPLA 2 s-IIA and -V activate intracellular cPLA 2 , which eventually releases AA in a selective manner. Indeed, this route is compatible with the recent studies using rat mesangial cells (77), human neutrophils (78), human astrocytoma (79), and mouse osteoblasts (19), in which sPLA 2 -IIA caused translational (19) or post-translational (77-79) activation of cPLA 2 , probably through the production of lipid mediators (19,77,78) or through the putative sPLA 2 receptor-dependent and catalysis-independent process (79). However, several lines of evidence argue against this speculation in our 293 cell system.…”
Section: Discussionsupporting
confidence: 70%
“…The simplest explanation for these events is that sPLA 2 s-IIA and -V activate intracellular cPLA 2 , which eventually releases AA in a selective manner. Indeed, this route is compatible with the recent studies using rat mesangial cells (77), human neutrophils (78), human astrocytoma (79), and mouse osteoblasts (19), in which sPLA 2 -IIA caused translational (19) or post-translational (77-79) activation of cPLA 2 , probably through the production of lipid mediators (19,77,78) or through the putative sPLA 2 receptor-dependent and catalysis-independent process (79). However, several lines of evidence argue against this speculation in our 293 cell system.…”
Section: Discussionsupporting
confidence: 70%
“…In addition, since the inhibitory effect of both snpPLA 2 and cPLA 2 inhibitors on [ 3 H]AA release is relieved by excess AA, we may suggest that snpPLA 2 and cPLA 2 upon cytokine stimulation act in a sequential manner, possibly in a positive feedback model. The AA metabolites LTB 4 , 5-oxoeicosatetraenoic acid, and 5-HETE has been found to activate cPLA 2 in neutrophils (63). We observed that the 5-LO inhibitor L-655,238 reduced cellular AA release by 85% in response to cytokines and that this effect was partially reversed by LTB 4 (Fig.…”
Section: -Lo Metabolites Mediate Tnf-␣-and Il-1␤-elicited Nf-b Activsupporting
confidence: 55%
“…We have recently shown that both snpPLA 2 and cPLA 2 , through AA-derived 5-LO metabolites as LTB 4 acting through its G-protein-coupled receptor in an autocrine feedback mechanism, contribute to activation of the immunomodulatory transcription factor NF-B in response to TNF-␣ and IL-1␤ (29). Other authors (62,63) have also described that snpPLA 2 and LTB 4 (acting in an autocrine fashion) increase AA release, cPLA 2 phosphorylation, and cPLA 2 activation. However, the mechanisms explaining how snpPLA 2 /LTB 4 regulate cPLA 2 activation is not understood in detail.…”
Section: Tnf-␣-or Il-1␤-induced Phosphorylation Of /Pkc and Cpla 2 Ismentioning
confidence: 99%